Preparation method for electroplating Ni-PTFE-coated PDA corrosion-resistant coating on aluminum alloy
By modifying PTFE particles and forming Ni-PTFE@PDA coating, the corrosion problem of aluminum alloy in humid environments is solved, and the corrosion resistance and stability of the coating are significantly improved.
Patent Information
- Application Number
- CN202510009702.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2045-01-03
AI Technical Summary
Aluminum alloys are prone to corrosion in humid environments containing Cl-, and traditional PTFE particles are unstable in the electroplating plating, limiting the corrosion resistance of the plating.
PTFE particles are modified by dopamine hydrochloride (DA) and the surface is coated with dopamine derivatives (PDA), which increases the dispersion stability of the particles in water, and forms a Ni-PTFE@PDA plating layer by complexing with metal Ni2+.
The content of PTFE particles in the plating layer and the corrosion resistance of the plating layer are improved, and the corrosion rate of the aluminum alloy is significantly reduced. The method is simple, economical and reliable.
Smart Images

Figure CN119615321A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of surface protection, and in particular relates to a method for preparing a corrosion-resistant coating of an aluminum alloy electroplated with Ni-PTFE@PDA. Background Art
[0002] Aluminum and its alloy materials are used in more and more fields due to their superior physical and chemical properties. However, aluminum alloy has an extremely low corrosion potential. In a humid environment containing Cl-, the surface of the aluminum alloy is easily corroded, which damages the aluminum alloy and related equipment, reduces the service life of the equipment, and causes certain economic losses.
[0003] PTFE particles have good corrosion resistance. Compounding PTFE particles into the coating can effectively improve the corrosion resistance of the coating. However, PTFE particles have extremely low surface energy and are difficult to be directly added to the plating solution for electroplating. The low compounding amount of PTFE particles in the electroplating coating also limits the improvement of the performance of the composite coating. Traditional plasma treatment, irradiation method, emulsion method and other treatment processes are complicated, the required equipment is expensive, and it is not easy to achieve an ideal dispersion state. Therefore, it is necessary to propose a new method to modify PTFE particles, improve the dispersion stability of PTFE particles in water, so that they can be stably dispersed in the plating solution, and increase the content of PTFE particles in the coating, so as to improve the corrosion resistance of aluminum alloy. Modifying PTFE with dopamine hydrochloride (DA) can solve the problem of stable dispersion of PTFE in the plating solution, and can improve the particle content in the coating and the corrosion resistance of the coating. This method has the advantages of simplicity, economy, easy operation and high reliability. Summary of the invention
[0004] An object of the present invention is to solve at least the above problems and / or disadvantages and to provide at least the advantages which will be described hereinafter.
[0005] In order to solve the above problems, the present invention provides a new PTFE particle modification method. PTFE is modified by DA, and a layer of PDA is coated on the surface of the particle. The hydrophilic groups such as hydroxyl and amino groups contained in PDA realize the stable dispersion of the particles in water. The catechol groups contained in PDA adsorb metal Ni 2+ A complex is formed, and PTFE@PDA is coated in the coating along with the reduction of metal Ni2+, thereby increasing the content of particles in the coating and improving the corrosion resistance of the aluminum alloy.
[0006] In order to achieve these purposes and other advantages according to the present invention, a method for preparing a corrosion-resistant coating of Ni-PTFE@PDA electroplated on an aluminum alloy is provided, comprising the following steps:
[0007] Step 1: Add PTFE nanoparticles to anhydrous ethanol, add polyethylene glycol monolaurate and mix evenly, make the particles initially hydrophilic, and then centrifuge for later use;
[0008] Step 2: Add the preliminarily hydrophilized PTFE nanoparticles to deionized water, and disperse them ultrasonically, add dopamine hydrochloride, tris(hydroxymethyl)aminomethane, and polyethylene glycol monolaurate, mix well, adjust the pH, add appropriate temperature and stir, polymerize in a dark environment, centrifuge, wash, and dry to obtain PTFE@PDA particles;
[0009] Step 3: Place the pretreated aluminum alloy substrate into a Watt plating solution containing PTFE@PDA particles for electroplating to obtain a Ni-PTFE@PDA corrosion-resistant coating.
[0010] Preferably, in the step 1, after uniform mixing, the concentration of PTFE nanoparticles is 20-30 g / L, and the concentration of polyethylene glycol monolaurate is 4-8 g / L.
[0011] Preferably, in the step 2, after uniform mixing, the concentration of the initially hydrophilic PTFE nanoparticles is 10-15 g / L, the concentration of dopamine hydrochloride is 1-3 g / L, the concentration of tris(hydroxymethyl)aminomethane is 10-20 g / L, and the concentration of polyethylene glycol monolaurate is 1-3 g / L.
[0012] Preferably, in the step 2, the pH is adjusted to 8.5, the appropriate temperature is 30-40° C., the stirring speed is 100-300 r / min; and the polymerization is carried out in a dark environment for 12-36 hours.
[0013] Preferably, the Watt plating solution is: NiSO4·6H2O 100-300g / L, NiCl2·6H2O 30-50g / L, H3BO3 20-40g / L, saccharin sodium 0.01-0.03g / L; the PTFE@PDA particle concentration is 7-8g / L, and the current density for electroplating is 0.01-0.08A / cm -1 , temperature is 40-50℃, stirring speed is 100-300r / min, and time is 1-2h.
[0014] Preferably, the preparation method of the pretreated aluminum alloy substrate comprises: sandpaper polishing, degreasing, acid etching, DA activation, and chemical Ni-P plating.
[0015] Preferably, the formula of DA activation is: 1-3 g / L dopamine hydrochloride, 10-20 g / L tris(hydroxymethyl)aminomethane; DA activation temperature 30-40°C, time 12-36 h, pH 8.5;
[0016] Preferably, the formula of the chemical Ni-P plating is: NiSO4 20-30 g / L, NaH2PO2 10-30 g / L, Na3C6H5O7 40-50 g / L, temperature 85-95°C, time 20-60 min.
[0017] The present invention also provides a Ni-PTFE@PDA corrosion-resistant coating prepared according to the above preparation method.
[0018] The present invention also provides an application of the Ni-PTFE@PDA corrosion-resistant coating prepared according to the above preparation method in the corrosion resistance of aluminum alloys.
[0019] The present invention has at least the following beneficial effects:
[0020] (1) The PTFE particle modification method adopted in the present invention increases the dispersion stability of PTFE particles in water, so that the PTFE particles can be stably dispersed in the plating solution, providing the possibility for composite electroplating. In addition, the catechol group on the surface of the modified PTFE@PDA particles is used to adsorb the main salt metal ions in the plating solution to form a complex, so that more particles are coated in the coating during composite electroplating, thereby improving the corrosion resistance of the aluminum alloy. Compared with traditional plasma, irradiation methods, etc., this method has the advantages of simple operation, economic and environmental protection, high reliability, etc., and can overcome the characteristics of low content of electroplated particles, maximize the original physical and chemical properties of the particles, improve the performance of the coating, and improve the protective effect on the substrate. In addition, this method can be analogous to other particulate materials. After the particles are wrapped with PDA, the particle content in the coating is increased by electroplating, chemical plating, etc.
[0021] (2) The modified PTFE@PDA particles of the present invention successfully achieved its dispersion stability in water, with a water contact angle of 30°. The PTFE content in the coating increased, with a volume fraction of 54%. In order to detect the corrosion resistance of the coating, the coating was subjected to potentiodynamic polarization curve analysis, electrochemical impedance spectroscopy (EIS) analysis and full immersion experiment. The results of the potentiodynamic polarization curve analysis showed that the self-corrosion potential of the Ni-PTFE@PDA coating reached -0.22E / V, which was 0.58E / V and 1.04E / V positively shifted compared with the aluminum alloy substrate and the Ni-P coating, respectively, and the corrosion current density decreased by 1 and 3 orders of magnitude, respectively. The EIS analysis results showed that the film resistance of the composite coating was higher in the corrosive medium. The results of the full immersion experiment showed that the corrosion rate of the composite coating was much lower than that of the aluminum alloy. In summary, the Ni-PTFE@PDA coating has good corrosion resistance.
[0022] Other advantages, objectives and features of the present invention will be embodied in part through the following description, and in part will be understood by those skilled in the art through study and practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the potentiodynamic polarization curve of the Ni-PTFE@PDA coating prepared in Example 1;
[0024] Figure 2 This is the electrochemical impedance spectroscopy of the Ni-PTFE@PDA coating prepared in Example 1;
[0025] Figure 3 The electrochemical impedance spectroscopy of the Ni-PTFE@PDA coating prepared in Example 1 (partial magnification);
[0026] Figure 4 This is a comparison chart of the 72-hour full immersion experiment of the Ni-PTFE@PDA coating prepared in the present invention. DETAILED DESCRIPTION
[0027] The present invention is further described in detail below in conjunction with the accompanying drawings so that those skilled in the art can implement the invention with reference to the description.
[0028] It should be understood that terms such as “having”, “including” and “comprising” used herein do not specify the existence or addition of one or more other elements or combinations thereof.
[0029] The present invention Figure 1 and Figure 2 Corrosion resistance test: The PGSTAT30 electrochemical workstation was used to carry out potentiodynamic polarization scanning test, with saturated calomel electrode (SCE) as reference electrode, platinum electrode as auxiliary electrode, and plated aluminum alloy (working surface 10mm×10mm) as working electrode. The test medium was 3.5wt% NaCl solution, and the test was started after the open circuit potential was stable, with a scanning rate of 0.02mV / s. The test range of AC impedance spectrum was 100Hz~0.01Hz, and the AC potential disturbance was 5mV.
[0030] The present invention utilizes a full immersion experiment to simulate the corrosion resistance of the composite coating in a marine environment. The tested solution is a NaCl solution with a mass fraction of 5%. The immersion time is 48 hours. The corrosion resistance of the coating is analyzed by observing the changes on the surface of the composite coating after immersion and calculating the corrosion rate of the composite coating by a weight loss method. Figure 4 The surface morphology of the composite coating before and after being immersed in a 5% NaCl solution for 48 hours is shown, and the corrosion rate is calculated based on the mass before and after corrosion.
[0031] Embodiment 1:
[0032] A method for preparing a corrosion-resistant coating of Ni-PTFE@PDA electroplated on an aluminum alloy comprises the following steps:
[0033] Step 1: Cut the commercially available aluminum alloy into 30mm×10mm×2mm rectangular blocks, polish, degrease, and acid-etch the aluminum alloy, and then put it into anhydrous ethanol to prevent the surface of the aluminum alloy from being oxidized again; use hydrochloric acid dopamine activation to replace the traditional aluminum alloy zinc immersion process, and put the treated aluminum alloy into the configured hydrochloric acid dopamine activation formula (dopamine hydrochloride (DA) 2g / L, tris (tris) 15g / L, temperature 35°C, time 24h, pH 8.5) for polymerization for 24 hours, then take it out for cleaning and drying;
[0034] Step 2: Place the activated aluminum alloy in a plating solution of 25 g / L NiSO4, 20 g / L NaH2PO2, and 45 g / L Na3C6H5O7, and perform chemical Ni-P plating in the plating solution at a temperature of 90°C. After 30 minutes, take out the aluminum alloy, clean it, blow it dry, and set it aside for later use.
[0035] Step 3, weigh PTFE particles and mix them with anhydrous ethanol, add polyethylene glycol monolaurate, mix them evenly (after mixing evenly, the concentration of PTFE nanoparticles is 24g / L, and the concentration of polyethylene glycol monolaurate is 6g / L), so that the particles are initially hydrophilic; the PTFE nanoparticles after initial hydrophilization are added to deionized water, and ultrasonically dispersed, and then dopamine hydrochloride, tris(hydroxymethylaminomethane) and polyethylene glycol monolaurate are added, and mixed evenly (after mixing evenly, the concentration of the PTFE nanoparticles after initial hydrophilization is 12g / L, the concentration of dopamine hydrochloride is 2g / L, the concentration of tris(hydroxymethylaminomethane) is 15g / L, and the concentration of polyethylene glycol monolaurate is 2g / L), adjust the pH to 8.5, the temperature to 35°C, the stirring speed to 200r / min, and polymerize in a dark environment for 24 hours, then centrifuge, wash and dry;
[0036] Step 4: Place the treated aluminum alloy into a Watt plating solution containing PTFE@PDA particles (NiSO4·6H2O 200 g / L, NiCl2·6H2O 40 g / L, H3BO3 30 g / L, saccharin sodium 0.01 g / L, PTFE@PDA particle concentration 7.5 g / L) for electroplating (current density 0.05 A / cm -1 , temperature 45 °C, stirring speed 200 r / min, time 1.5 h), Ni-PTFE@PDA corrosion-resistant coating was obtained, and the corrosion rate was 0.052 g·h -1 ·m -2 .
[0037] like Figure 1 The self-corrosion potential of the Ni-PTFE@PDA coating reaches -0.22E / V, which is 0.58E / V and 1.04E / V more positive than that of the aluminum alloy substrate and the Ni-P coating, respectively, and the corrosion current density decreases by 1 and 3 orders of magnitude, respectively;
[0038] like Figure 2 The EIS analysis results shown indicate that the composite coating has a higher film resistance in the corrosive medium;
[0039] Embodiment 2:
[0040] A method for preparing a corrosion-resistant coating of Ni-PTFE@PDA electroplated on an aluminum alloy comprises the following steps:
[0041] Step 1: Cut the commercially available aluminum alloy into 30mm×10mm×2mm rectangular blocks, polish, degrease, and acid-etch the aluminum alloy, and then put it into anhydrous ethanol to prevent the surface of the aluminum alloy from being oxidized again; use hydrochloric acid dopamine activation to replace the traditional aluminum alloy zinc immersion process, and put the treated aluminum alloy into the configured hydrochloric acid dopamine activation formula (dopamine hydrochloride (DA) 2g / L, tris (tris) 15g / L, temperature 35°C, time 24h, pH 8.5) for polymerization for 24 hours, then take it out for cleaning and drying;
[0042] Step 2: Place the activated aluminum alloy in a plating solution of 25 g / L NiSO4, 20 g / L NaH2PO2, and 45 g / L Na3C6H5O7, and perform chemical Ni-P plating in the plating solution at a temperature of 90°C. After 30 minutes, take out the aluminum alloy, clean it, blow it dry, and set it aside for later use.
[0043] Step 3, weigh PTFE particles and mix them with anhydrous ethanol, add polyethylene glycol monolaurate, mix them evenly (after mixing evenly, the concentration of PTFE nanoparticles is 24g / L, and the concentration of polyethylene glycol monolaurate is 6g / L), so that the particles are initially hydrophilic; the PTFE nanoparticles after initial hydrophilization are added to deionized water, and ultrasonically dispersed, and then dopamine hydrochloride, tris(hydroxymethylaminomethane) and polyethylene glycol monolaurate are added, and mixed evenly (after mixing evenly, the concentration of the PTFE nanoparticles after initial hydrophilization is 12g / L, the concentration of dopamine hydrochloride is 2g / L, the concentration of tris(hydroxymethylaminomethane) is 15g / L, and the concentration of polyethylene glycol monolaurate is 2g / L), adjust the pH to 8.5, the temperature to 25°C, the stirring speed to 200r / min, and polymerize in a dark environment for 24 hours, then centrifuge, wash and dry;
[0044] Step 4: Place the treated aluminum alloy into a Watt plating solution containing PTFE@PDA particles (NiSO4·6H2O 200 g / L, NiCl2·6H2O 40 g / L, H3BO3 30 g / L, saccharin sodium 0.01 g / L, PTFE@PDA particle concentration 7.5 g / L) for electroplating (current density 0.05 A / cm -1, temperature 45 °C, stirring speed 200 r / min, time 1.5 h), Ni-PTFE@PDA corrosion-resistant coating was obtained, and the corrosion rate was 0.061 g·h -1 ·m -2 .
[0045] The water contact angle of the Ni-PTFE@PDA corrosion-resistant coating prepared in this example is 46.311°.
[0046] Embodiment 3:
[0047] A method for preparing a corrosion-resistant coating of Ni-PTFE@PDA electroplated on an aluminum alloy comprises the following steps:
[0048] Step 1: Cut the commercially available aluminum alloy into 30mm×10mm×2mm rectangular blocks, polish, degrease, and acid-etch the aluminum alloy, and then put it into anhydrous ethanol to prevent the surface of the aluminum alloy from being oxidized again; use hydrochloric acid dopamine activation to replace the traditional aluminum alloy zinc immersion process, and put the treated aluminum alloy into the configured hydrochloric acid dopamine activation formula (dopamine hydrochloride (DA) 2g / L, tris (tris) 15g / L, temperature 35°C, time 24h, pH 8.5) for polymerization for 24 hours, then take it out for cleaning and drying;
[0049] Step 2: Place the activated aluminum alloy in a plating solution of 25 g / L NiSO4, 20 g / L NaH2PO2, and 45 g / L Na3C6H5O7, and perform chemical Ni-P plating in the plating solution at a temperature of 90°C. After 30 minutes, take out the aluminum alloy, clean it, blow it dry, and set it aside for later use.
[0050] Step 3, weigh the PTFE particles and mix them with anhydrous ethanol, add polyethylene glycol monolaurate, mix them evenly (after mixing evenly, the concentration of PTFE nanoparticles is 24g / L, and the concentration of polyethylene glycol monolaurate is 6g / L), so that the particles are initially hydrophilic; the PTFE nanoparticles after initial hydrophilization are added to deionized water, and ultrasonically dispersed, and then dopamine hydrochloride, tris(hydroxymethylaminomethane) and polyethylene glycol monolaurate are added, and mixed evenly (after mixing evenly, the concentration of the PTFE nanoparticles after initial hydrophilization is 12g / L, the concentration of dopamine hydrochloride is 2g / L, the concentration of tris(hydroxymethylaminomethane) is 15g / L, and the concentration of polyethylene glycol monolaurate is 2g / L), adjust the pH to 8.5, the temperature to 45°C, the stirring speed to 200r / min, and centrifuge, wash and dry after polymerization in a dark environment for 24 hours;
[0051] Step 4: Place the treated aluminum alloy into a Watt plating solution containing PTFE@PDA particles (NiSO4·6H2O 200 g / L, NiCl2·6H2O 40 g / L, H3BO3 30 g / L, saccharin sodium 0.01 g / L, PTFE@PDA particle concentration 7.5 g / L) for electroplating (current density 0.05 A / cm -1 , temperature 45 °C, stirring speed 200 r / min, time 1.5 h), Ni-PTFE@PDA corrosion-resistant coating was obtained, and the corrosion rate was 0.154 g·h -1 ·m -2 .
[0052] The water contact angle of the Ni-PTFE@PDA corrosion-resistant coating prepared in this example is 67.865°.
[0053] Embodiment 4:
[0054] A method for preparing a corrosion-resistant coating of Ni-PTFE@PDA electroplated on an aluminum alloy comprises the following steps:
[0055] Step 1: Cut the commercially available aluminum alloy into 30mm×10mm×2mm rectangular blocks, polish, degrease, and acid-etch the aluminum alloy, and then put it into anhydrous ethanol to prevent the surface of the aluminum alloy from being oxidized again; use hydrochloric acid dopamine activation to replace the traditional aluminum alloy zinc immersion process, and put the treated aluminum alloy into the configured hydrochloric acid dopamine activation formula (dopamine hydrochloride (DA) 2g / L, tris (tris) 15g / L, temperature 35°C, time 24h, pH 8.5) for polymerization for 24 hours, then take it out for cleaning and drying;
[0056] Step 2: Place the activated aluminum alloy in a plating solution of 25 g / L NiSO4, 20 g / L NaH2PO2, and 45 g / L Na3C6H5O7, and perform chemical Ni-P plating in the plating solution at a temperature of 90°C. After 30 minutes, take out the aluminum alloy, clean it, blow it dry, and set it aside for later use.
[0057] Step 3, weigh PTFE particles and mix them with anhydrous ethanol, add polyethylene glycol monolaurate, mix them evenly (after mixing evenly, the concentration of PTFE nanoparticles is 24g / L, and the concentration of polyethylene glycol monolaurate is 6g / L), so that the particles are initially hydrophilic; the PTFE nanoparticles after initial hydrophilization are added to deionized water, and ultrasonically dispersed, and then dopamine hydrochloride, tris(hydroxymethylaminomethane) and polyethylene glycol monolaurate are added, and mixed evenly (after mixing evenly, the concentration of the PTFE nanoparticles after initial hydrophilization is 12g / L, the concentration of dopamine hydrochloride is 2g / L, the concentration of tris(hydroxymethylaminomethane) is 15g / L, and the concentration of polyethylene glycol monolaurate is 2g / L), adjust the pH to 8.5, the temperature to 35°C, the stirring speed to 200r / min, and polymerize in a dark environment for 24 hours, then centrifuge, wash and dry;
[0058] Step 4: Place the treated aluminum alloy into a Watt plating solution containing PTFE@PDA particles (NiSO4·6H2O 200 g / L, NiCl2·6H2O 40 g / L, H3BO3 30 g / L, saccharin sodium 0.01 g / L, PTFE@PDA particle concentration 7.5 g / L) for electroplating (current density 0.07 A / cm -1 , temperature is 45°C, stirring speed is 200r / min, time is 2h), and Ni-PTFE@PDA corrosion-resistant coating is obtained.
[0059] like Figure 4 The experimental results shown in Table 1 show that aluminum alloy ( Figure 4 The corrosion rate of the sample on the left reached 2.207 g·h -1 ·m -2 ; The Ni-PTFE@PDA corrosion-resistant coating prepared in this embodiment ( Figure 4 The corrosion rate of the sample on the right is 0.074 g·h -1 ·m -2 In summary, the Ni-PTFE@PDA coating has good corrosion resistance.
[0060] Table 1
[0061]
[0062] Embodiment 5:
[0063] A method for preparing a corrosion-resistant coating of Ni-PTFE@PDA electroplated on an aluminum alloy comprises the following steps:
[0064] Step 1: Cut the commercially available aluminum alloy into 30mm×10mm×2mm rectangular blocks, polish, degrease, and acid-etch the aluminum alloy, and then put it into anhydrous ethanol to prevent the surface of the aluminum alloy from being oxidized again; use hydrochloric acid dopamine activation to replace the traditional aluminum alloy zinc immersion process, and put the treated aluminum alloy into the configured hydrochloric acid dopamine activation formula (dopamine hydrochloride (DA) 2g / L, tris (tris) 15g / L, temperature 35°C, time 24h, pH 8.5) for polymerization for 24 hours, then take it out for cleaning and drying;
[0065] Step 2: Place the activated aluminum alloy in a plating solution of 25 g / L NiSO4, 20 g / L NaH2PO2, and 45 g / L Na3C6H5O7, and perform chemical Ni-P plating in the plating solution at a temperature of 90°C. After 30 minutes, take out the aluminum alloy, clean it, blow it dry, and set it aside for later use.
[0066] Step 3, weigh PTFE particles and mix them with anhydrous ethanol, add polyethylene glycol monolaurate, mix them evenly (after mixing evenly, the concentration of PTFE nanoparticles is 24g / L, and the concentration of polyethylene glycol monolaurate is 6g / L), so that the particles are initially hydrophilic; the PTFE nanoparticles after initial hydrophilization are added to deionized water, and ultrasonically dispersed, and then dopamine hydrochloride, tris(hydroxymethylaminomethane) and polyethylene glycol monolaurate are added, and mixed evenly (after mixing evenly, the concentration of the PTFE nanoparticles after initial hydrophilization is 12g / L, the concentration of dopamine hydrochloride is 2g / L, the concentration of tris(hydroxymethylaminomethane) is 15g / L, and the concentration of polyethylene glycol monolaurate is 2g / L), adjust the pH to 8.5, the temperature to 35°C, the stirring speed to 200r / min, and polymerize in a dark environment for 24 hours, then centrifuge, wash and dry;
[0067] Step 4: Place the treated aluminum alloy into a Watt plating solution containing PTFE@PDA particles (NiSO4·6H2O 200 g / L, NiCl2·6H2O 40 g / L, H3BO3 30 g / L, saccharin sodium 0.01 g / L, PTFE@PDA particle concentration 10 g / L) for electroplating (current density 0.08 A / cm -1 , temperature is 45°C, stirring speed is 200r / min, time is 1.5h), and Ni-PTFE@PDA corrosion-resistant coating is obtained.
[0068] The corrosion rate of the Ni-PTFE@PDA corrosion-resistant coating prepared in this example is 0.075 g·h -1 ·m -2 .
[0069] Although the embodiments of the present invention have been disclosed as above, they are not limited to the applications listed in the specification and the implementation modes, and they can be fully applied to various fields suitable for the present invention. For those familiar with the art, additional modifications can be easily implemented. Therefore, without departing from the general concept defined by the claims and the scope of equivalents, the present invention is not limited to the specific details and the illustrations shown and described herein.
Claims
1. A method for preparing a corrosion-resistant coating of Ni-PTFE@PDA electroplated on aluminum alloy, characterized in that: The following steps are involved: Step 1: Add PTFE nanoparticles to anhydrous ethanol, add polyethylene glycol monolaurate and mix evenly, make the particles initially hydrophilic, and then centrifuge for later use; Step 2: Add the preliminarily hydrophilized PTFE nanoparticles to deionized water, and disperse them ultrasonically, add dopamine hydrochloride, tris(hydroxymethyl)aminomethane, and polyethylene glycol monolaurate, mix well, adjust the pH, add appropriate temperature and stir, polymerize in a dark environment, centrifuge, wash, and dry to obtain PTFE@PDA particles; Step 3: Place the pretreated aluminum alloy substrate into a Watt plating solution containing PTFE@PDA particles for electroplating to obtain a Ni-PTFE@PDA corrosion-resistant coating.
2. The method for preparing the corrosion-resistant coating of aluminum alloy electroplated Ni-PTFE@PDA according to claim 1, characterized in that: In the step 1, after uniform mixing, the concentration of PTFE nanoparticles is 20-30 g / L, and the concentration of polyethylene glycol monolaurate is 4-8 g / L.
3. The method for preparing the corrosion-resistant coating of aluminum alloy electroplated Ni-PTFE@PDA according to claim 1, characterized in that: In the step 2, after uniform mixing, the concentration of the initially hydrophilic PTFE nanoparticles is 10-15 g / L, the concentration of dopamine hydrochloride is 1-3 g / L, the concentration of tris(hydroxymethyl)aminomethane is 10-20 g / L, and the concentration of polyethylene glycol monolaurate is 1-3 g / L.
4. The method for preparing the corrosion-resistant coating of aluminum alloy electroplated Ni-PTFE@PDA according to claim 1, characterized in that: In the step 2, the pH is adjusted to 8.5, the appropriate temperature is 30-40° C., and the stirring speed is 100-300 r / min; polymerization is carried out in a dark environment for 12-36 hours.
5. The method for preparing the corrosion-resistant coating of aluminum alloy electroplated Ni-PTFE@PDA according to claim 1, characterized in that: The Watt plating solution is: NiSO4·6H2O 100-300g / L, NiCl2·6H2O 30-50g / L, H3BO3 20-40g / L, saccharin sodium 0.01-0.03g / L; the PTFE@PDA particle concentration is 7-8g / L, and the current density for electroplating is 0.01-0.08A / cm -1 , temperature is 40-50℃, stirring speed is 100-300r / min, and time is 1-2h.
6. The method for preparing the corrosion-resistant coating of aluminum alloy electroplated Ni-PTFE@PDA according to claim 1, characterized in that: The preparation method of the pretreated aluminum alloy substrate comprises: sandpaper polishing, degreasing, acid etching, DA activation, and chemical Ni-P plating.
7. The method for preparing the corrosion-resistant coating of aluminum alloy electroplated Ni-PTFE@PDA according to claim 6, characterized in that: The formula of DA activation is: 1-3 g / L dopamine hydrochloride, 10-20 g / L tris(hydroxymethyl)aminomethane; the temperature of DA activation is 30-40° C., the time is 12-36 h, and the pH is 8.
5.
8. The method for preparing the corrosion-resistant coating of aluminum alloy electroplated with Ni-PTFE@PDA according to claim 6, characterized in that: The formula of the chemical Ni-P plating is: NiSO4 20-30g / L, NaH2PO2 10-30g / L, Na3C6H5O7 40-50g / L, temperature 85-95°C, time 20-60min.
9. A Ni-PTFE@PDA corrosion-resistant coating prepared according to the preparation method according to any one of claims 1 to 8.
10. Application of the Ni-PTFE@PDA corrosion-resistant coating prepared by the preparation method according to any one of claims 1 to 8 in the corrosion resistance of aluminum alloy.
Citation Information
Patent Citations
PTFE microfiltration membrane and hydrophilic modification method of PTFE microfiltration membrane
CN113694739A
Water-based polytetrafluoroethylene artificial granite composite material and preparation method thereof
CN118667396A
Coatings Having Enhanced Corrosion Performance and Method of Using the Same
US20130216720A1